Pengaruh Gaya Kepemimpinan dan Motivasi Terhadap Peningkatan Kinerja Karyawan Bagian Distribusi Pada PT. Indomarco Adi Prima Cab. Ngadiluwih - Astuti, Rini (Akutansi Bisnis & Manajemen ( ABM ), 2018)
The purpose of this research are: (1) To examine the extent to which influence Motivation (X2) on Employee Performance Distribution Department at PT. IndomarcoAdi Prima, Ngadiluwih; (2) To know the variables X (leadership style (X1), Motivation (X2)) which have the dominant influence on variable Y (Employee Performance) at PT. Indomarcoadi Prima Ngadiluwih. The sample in this research are all employees at PT Indomarco Adi Prima cabang Ngadiluwih because the number is relatively small (42 peoples). The influence of leadership style and motivation on employee performance at PT Indomarco Adi Prima Cab.Ngadiluwih (R) is 0843. It shows they have strong closeness, to the performance so that influenced by leadership style and motivation equal to 84,3% while the rest influenced by other factor.